Activity of transition metals in N‐doped carbon Electrocatalysts for hydrogen evolution reaction: Insight from quantum chemistry computations. (15th September 2021) - Baghban, Alireza; Habibzadeh, Sajjad; Zokaee Ashtiani, Farzin
Summary: Owning to growing trends in global environmental and energy concerns, great efforts have been carried out to find environmentally friendly sources of energy. Hydrogen production from the water‐splitting process by hydrogen evolution reaction (HER) is a promising approach, but it needs commercially expensive Pt‐based electrocatalysts. Hence, designing nonnoble‐metal catalysts for this reaction with both great activity and robust stability has remained a crucial challenge in the past decades. In the present study, platinum (Pt), nickel (Ni), cobalt (Co), manganese (Mn), and copper (Cu) metals are uniformly considered on N‐doped carbon (NC) nanosheet derived from zeolitic imidazolate metal–organic framework (ZIF), and the capability of proposed nanomaterials is theoretically investigated by density functional theory (DFT) for HER process. As expected, results indicate Pt/NC has a high ability for HER process. Besides, it was shown that energy barriers in the HER process catalyzed by Ni and Co /NC electrocatalysts were close to zero representing their great HER activity. Abstract : In this paper activity of metal NC composites containing transition metals such as nickel, cobalt, manganese, and copper was investigated theoretically by DFT approach and their performance was compared with Pt/NC structure.